Rural underdevelopment in the former Ciskei with specific reference to Glenmore Village - Malila, Brett (Rhodes University, Faculty of Humanities, Department of Sociology, 2000)
This thesis examines development changes that took place in Glenmore after 1994. To examine such change one needs to have a concise historical understanding of the situation in Glenmore before democracy. The aim of the work is to critique development at a local, rural level, pinpointing the major changes, if any, that came with the incorporation of the former homeland of Ciskei (and thus Glenmore village) with South Africa. These people were forcibly resettled in 1979 for political and economic reasons. Their situation then was one of dire poverty; it is argued here that even with democracy, their history of underdevelopment has continued. The reason for this continued underdevelopment is the structure of the former reserves. The overall political context has changed in South Africa but the most important aspect with regard to the development of the homelands: land, has not. At the central level, the government has churned out a wide variety of development policies, which due to the prevailing political and economic context of the times are fraught with inconsistencies. The example used here to show some of these inconsistencies is the 1997 White Paper on Land Reform. This confusion at the central level with regard to the perceived future of South Africa has managed to adversely affect the rural areas and their development. There very well might be policies in abundance to improve the life-world of the rural poor, but there are inconsistencies between this policy and actual practice. With regard to Glenmore the confusion in the present government's central development policy is arguably the main reason for the underdevelopment of the village. The inconsistencies in policy such as the 1997 White Paper on Land Reform, have meant that the structure of the reserves has not changed. Vital issues such as land tenure and ownership have not been dealt with. The study thus shows that unless the structure of the homeland system which is predominantly based on issues of land, is changed, genuine social and economic development will not take place in areas like Glenmore.
Keywords: Rural development -- South Africa -- Eastern Cape; Poverty -- South Africa -- Eastern Cape; Eastern Cape (South Africa) -- Social conditions; Glenmore (South Africa) -- Economic conditions